The PLC control of an electrical system consisting of an electromagnetically sliding brake and coupling - Gabor, Georgel (JET on-line, 2018)
This paper describes an electrical system consisting of electrical sliding coupling driven by a 3 phase electric motor and electric sliding brake. A frequency converter provides control of the motor. Furthermore, the communication between PLC and frequency converter is done using PROFIBUS communication. The data are displayed on a SIEMENS HMI display. The goal is to control the electrical sliding coupling, which is mechanically connected to the electrical sliding brake.
Keywords: electromagnetically sliding brake; electromagnetically sliding couple; električne drsne zavore; električni drsni sklop; električni sistemi; frekvenčni pretvornik; industrial communication; PLC; PLC krmilnik; PROFIBUS; variable frequency converter; vodenje